SUBSTANCE OF AMULETS AND CULTURAL DUTY: Received: 10th March 2023; Revised: 28th June 2023, 31st July 2023; Accepted: 08th August 2023 - Junpitakchai, Jantra (PEOPLE: International Journal of Social Sciences, 2023)
Since ancient times, each culture had an object called an “amulet” as a spiritual anchor to protect people from negative energy, evil, and injury. Humans were born in the world, and they need to confront many things for living their lives and survival. These things occurred with fear, pain, suffering, and others. Hence, amulets were created to strengthen mental power for getting ready to fight against what humans were unable to overcome. Humane belief in amulets has been passed down from generation to generation until today, the era of technological advancement and goodness. Those prosperities are a tool that humans can use to eliminate problems and feelings reasonably, such as small Buddha images, amulets, and symbols in different forms. Thus, this article aims to reveal knowledge or some theoretical opinions to support the legitimacy of amulet art containing history, art, culture, and phenomena by proof and references from research studies that present the importance of objects or amulet art in terms of how they have an effect or produce any factor on humans and what is the main purpose of amulet art that can be proven by scientific theories (scientific tools) from utilization and mental development and restoration rather than credulity.